Hubungan Pola Asuh Permissive Terhadap Kenakalan Remaja di SMK Muhammadiyah 8 Banyuwangi - Putri, Millenia Zaskia; Ervina, Iin Dwi; Sari, Anggraeni Swastika (Indonesian Journal Publisher, 2024)
Support from the family is very important because it can influence the emergence of juvenile delinquency, because parental monitoring can determine the formation of behavior/character in children when they grow up. The aim of this research is to determine the relationship between permissive parenting patterns and juvenile delinquency at SMK Muhammadiyah 8 Banyuwangi. This research uses a correlational approach with quantitative methods. The subjects in this research were teenagers in classes X and the permissive parenting style scale uses a Likert scale with a validity value of 0.692 and a reliability of 0.900. The data analysis technique used is product moment. The results of the research show that there is a positive relationship between permissive parenting and juvenile delinquency at SMK Muhammadiyah 8 Banyuwangi with a correlation value of 0.553 with a significance level of 0.000. The relative contribution made by permissive parenting to juvenile delinquency is r²=0.306, of which permissive parenting contributes 30.6%, the rest is influenced by other factors.